2004
DOI: 10.1590/s0037-86822004000400002
|View full text |Cite
|
Sign up to set email alerts
|

A epidemia de dengue/dengue hemorrágico no município do Rio de Janeiro, 2001/2002

Abstract: The following study was intended to evaluate the occurrence of typical signs and symptoms in the cases of classic dengue and hemorrhagic dengue fever, during the 2001-2002 epidemic in the city of Rio de Janeiro. The authors reviewed 155,242 cases notified to the Information System of Notification Diseases, from January/2001 to June/2002: 81,327 cases were classified as classic dengue and 958 as hemorrhagic dengue fever, with a total of 60 deaths. Common symptoms, such as fever, headache, prostration, myalgia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 9 publications
1
13
0
12
Order By: Relevance
“…8 The results obtained by means of the calculation of Moran's global index for the studied variables expressed statistically significant auto-correlation. Besides, the analysis of the local auto-correlation indicators of the average incidence rate of dengue showed the existence of spatial dependence for 41 neighborhoods of the municipality of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 89%
“…8 The results obtained by means of the calculation of Moran's global index for the studied variables expressed statistically significant auto-correlation. Besides, the analysis of the local auto-correlation indicators of the average incidence rate of dengue showed the existence of spatial dependence for 41 neighborhoods of the municipality of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the gender of the patients, Rodrigues, Scander and Casali showed in their studies that there were no statistically significant differences, as also seen in Ceará in 2003 [7][8][9] . On the other hand, Montenegro, investigating 14 patients who progressed to death in Recife, suggested that male gender predominated 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in India showed that the most frequent type of bleeding was gastrointestinal (34.5%), followed by petechiae (23.6%) and pulmonary bleeding (13.6%) 13 . During an epidemic in Rio de Janeiro in 2001 and 2002, the most common hemorrhagic manifestations were petechiae (51.6%), digestive hemorrhage (37.6%), gingivorrhagia (34.6%) and epistaxis (34.1%) 7 . In this same study, some signs and risk symptoms for evolution of hemorrhagic cases were identified, such as nausea, abdominal pain, petechiae, epistaxis, gingivorrhagia, hepatomegaly, digestive hemorrhage, shock, ascites and pleural effusion 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Porém, nos meses considerados quentes, há uma elevação da temperatura, dos índices pluviométricos e da umidade rela va do ar, fatores ambientais altamente propícios à proliferação do vetor da dengue (CASALI et al, 2004).…”
Section: Discussionunclassified